REAL TIME ROOM AUTOMATION USING IOT DEVICE (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
The project aims to design an advanced Room automation system using Wireless technology. The devices can be switched ON/OFF using an Android phone through Wireless Technology - IOT. Automation is the most frequently spelled term in the field of electronics. The hunger for automation brought many revolutions in the existing technologies. These had greater importance than any other technologies due to their user-friendly nature. These can be used as a replacement for the existing switches in Room which produces sparks and also results in fire accidents in few situations. The proposed system develops the Wireless Technology – IOT based advanced automation system to control the appliances in the Room. Wireless Technology - IOT is a wireless technology that uses radio frequency to transmit data through the air. Wireless Technology - IOT has initial speeds of 1mbps to 2mbps. Wireless Technology – IOT transmits data in the frequency band of 2.4 GHz. Range of Wireless Technology – IOT technology is 40-300 feet. The controlling device for the automation in the project is a Microcontroller. The data sent from Mobile phone over Wireless Technology - IOT. Microcontroller reads the data and decides the switching action of electrical devices connected to it through Relay switches. All components are associated to micro controller Arduino. Arduino ESP8266 micro controller is used to process input and produce output by using ARDUINO IDE with Embedded C programming and operated through Regulated power supply which gives 5v of DC voltage to all hardware modules.